1997
DOI: 10.1111/1523-1747.ep12340652
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sunscreens on UVB-Induced Immunomodulation in Humans

Abstract: Ultraviolet radiation has been shown to suppress the (skin) immune system both in animal species and in humans. Whether sunscreens can prevent immunosuppression is a matter of debate. This study investigated the protective capacity of a commercial sunscreen lotion in humans. Part of the right arm of healthy volunteers was exposed to erythemagenic ultraviolet B doses of 160 mJ per cm2 for four consecutive days. Before irradiation, sunscreen was applied either directly onto the skin or onto a piece of quartz fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Functional restoration of alloantigen presentation to T cells by epidermal cells from in vivo ‐UVA1 and UVB‐exposed skin occurred in each of several experiments to at least a partial level (Table 3) (23, 35, 36), except when UVB was chronically applied thrice‐weekly over 4 weeks (37, 38). Thus, chronic exposure may not be modeled well by acute exposure, UV dose escalation may exceed sunscreen capacities, or compliance issues may come into play.…”
Section: Antigen‐presenting Cells (Apcs) Functional Capacity and Enummentioning
confidence: 99%
See 1 more Smart Citation
“…Functional restoration of alloantigen presentation to T cells by epidermal cells from in vivo ‐UVA1 and UVB‐exposed skin occurred in each of several experiments to at least a partial level (Table 3) (23, 35, 36), except when UVB was chronically applied thrice‐weekly over 4 weeks (37, 38). Thus, chronic exposure may not be modeled well by acute exposure, UV dose escalation may exceed sunscreen capacities, or compliance issues may come into play.…”
Section: Antigen‐presenting Cells (Apcs) Functional Capacity and Enummentioning
confidence: 99%
“…With regard to LC numbers, most studies revealed an incomplete protection against UV‐induced LC depletion (19, 23, 39). In one study using UVB, UV‐induced infiltration of macrophages was reversed by sunscreen, as was their associated APC functional activity (Table 3) (37). In none of these studies was a dose range of UV administered to determine an IPF‐APC (Fxn or #) and none used SSR.…”
Section: Antigen‐presenting Cells (Apcs) Functional Capacity and Enummentioning
confidence: 99%
“…The main product of the histidine-to-urocanic acid pathway plays an important role in skin physiology by maintaining SC hydration and affecting ultraviolet protection. [16][17][18] The products of the phospholipid-to-free fatty acid pathway are free fatty acids, which not only influence the normal SC acidification, but also play an important role in the dual functions of SC integrity and cohesion. 9 Lipids in the SC are known to play a decisive role in maintaining the barrier function of the skin.…”
mentioning
confidence: 99%
“…More than one million new cases of nonmelanoma skin cancer will be diagnosed in the United States this year. 9,10 The burning question of course is, do sunscreens prevent skin cancer? As sunlight has been implicated as the major environmental agent that causes skin cancer, we have sought ways to reduce the risk of developing skin cancer without compromising our love affair with the great outdoors.…”
mentioning
confidence: 99%
“…8 Therefore it is important to recognize that sunscreens do not completely prevent UV-induced immunosuppression, and that the UV threshold for immunosuppression is lower than for erythema. 9,10 The burning question of course is, do sunscreens prevent skin cancer? There are data to support the notion that high-SPF sunscreens can reduce the risk of actinic keratoses 11,12 and squamous cell carcinomas.…”
mentioning
confidence: 99%